1999
DOI: 10.1016/s0014-5793(99)00408-1
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative interaction of NF‐κB and C/EBP binding sites is necessary for manganese superoxide dismutase gene transcription mediated by lipopolysaccharide and interferon‐γ

Abstract: Expression of the manganese superoxide dismutase (Mn-SOD) is induced by pro-inflammatory cytokines. We investigated the cis-acting elements within a tumor necrosis factor-responsive element (TNFRE) which was identified in the second intron of the murine Mn-SOD gene. Site-directed mutagenesis, reporter plasmid transfection studies and electrophoretic mobility shift assays demonstrated that inducible transcription factors enhanced the transcriptional activity of the Mn-SOD gene through the TNFRE. The cooperation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
3
34
0
Order By: Relevance
“…We also demonstrate that activation of CEBP/␤ in addition to NF-B is a mechanism leading to synergistic induction of MnSOD by PMA and cytokines (41). Our results are also consistent with reports that demonstrate that NF-B is a potential transcription factor activated simultaneously with other transcription factors, such as C/EBP upon stimulation by cytokines, producing cross-talk between them to maximize gene induction (30,48). In this present report we confirm the synergistic induction of the SOD2 gene in a hepatocarcinoma cell line, and extend the observation to include p50 and p65, c-Rel, another NF-B protein of the Rel family, in the synergistic induction process.…”
Section: Discussionsupporting
confidence: 91%
“…We also demonstrate that activation of CEBP/␤ in addition to NF-B is a mechanism leading to synergistic induction of MnSOD by PMA and cytokines (41). Our results are also consistent with reports that demonstrate that NF-B is a potential transcription factor activated simultaneously with other transcription factors, such as C/EBP upon stimulation by cytokines, producing cross-talk between them to maximize gene induction (30,48). In this present report we confirm the synergistic induction of the SOD2 gene in a hepatocarcinoma cell line, and extend the observation to include p50 and p65, c-Rel, another NF-B protein of the Rel family, in the synergistic induction process.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, it has been reported that cotransfection of NFB p65 and C/EBP␤ induces a synergistic activation of the interleukin (IL)-6 and IL-8 promoters (28,31,32), by means of a direct interaction between the b-Zip domain of C/EBP␤ and the Rel homology domain of NFB p65 (28). In very few instances, such a synergistic effect of NFB p65 and C/EBP␤ on gene transcription has been reported in response to inflammatory mediators: this is the case for genes encoding the manganese superoxide dismutase (33), the coagulation factor VIII (34), and the serum amyloid A1 protein (35,36), in response to LPS/interferon-␥, LPS, and LPS/IL-1/IL-6, respectively. Interestingly, a similar synergy between NFB p65 and C/EBP␤, but in response to TNF␣, has been observed in the transcriptional regulation of the cyclooxygenase-2 (37), the granulocyte colony-stimulating factor (38), and the intercellular adhesion molecule-1 (39,40) genes, three sequences that, like MEFV, are expressed by cells directly involved in inflammatory processes.…”
Section: Discussionmentioning
confidence: 99%
“…p52 partially substitutes for the lack of p50 and cRel for the lack of p65 (Hoffmann et al, 2003). C/EBPb and NF-kB cooperatively bind and activate the IL-6, IL-8, G-CSF, serum amyloid, intercellular adhesion molecule 1, superoxide dismutase and Mediterranean fever promoters during the inflammatory response in myeloid and other cells (Dunn et al, 1994;Kunsch et al, 1994;Xia et al, 1997;Maehara et al, 1999;Papin et al, 2003). Co-immunoprecipitation demonstrates interaction of bacterially expressed C/EBPa or C/EBPb with bacterially expressed or in vitro translated p50 or p65, mapping to the bZIP domain of C/EBP and to the Rel homology domain of p65 (Matsusaka et al, 1993;Stein et al, 1993).…”
Section: Nf-jb and Interaction With C/ebpmentioning
confidence: 99%